Pemeriksaan Status Gizi dan Edukasi Pencegahan Diabetes Melitus terhadap Lansia di Wilayah Putukrejo, Desa Peniwen, Kabupaten Malang - Nadia Refina Tiurlan Barasa; Hanna Tabita Hasianna Silitonga; Evelyn Danielle Wijaya; Harum Nida'ul Husna; Bimo Rafi Prayogo; Indira Xena Salvita; Lisa Rahmawati; Minarni Wartiningsih; Ni Djoman Juliasih; Isnaini Isnaini (Jurnal Abdimas Kesehatan (JAK), 2023)
The number of elderly people in Indonesia is increasing from year to year. The increasing age of the elderly, as well as the increasing prevalence of diabetes mellitus in the elderly, are the result of neurohormonal changes, lifestyle changes, decreased physical activity, changes in body composition, and increased oxidative stress. The goal of this community service is to provide health services in the form of nutritional assessments for the elderly and education to increase the elderly's knowledge in Peniwen Village, Malang Regency. Community service activities begin with screening Upper Arm Circumference, Abdominal Circumference, Height, Weight, Body Mass Index, Blood Pressure, and Random Blood Sugar levels in the elderly. Counseling was then provided to 20 people using powerpoint media, brochures, and booklets. The information provided included diabetes mellitus, risk factors, random blood sugar levels, and diabetes mellitus prevention. The level of knowledge of respondents is assessed using pre-test and post-test instruments. According to the results of the pre-test and post-test conducted by the elderly in Putukrejo Hamlet, educational methods in the form of presentations, booklets, and brochures containing material about Diabetes Mellitus, risk factors for events, measurement of blood sugar levels in the elderly, and diabetes mellitus prevention went as expected, namely a 40% increase.